MORPHOLOGICAL CHANGES OF THE BRAIN CORTEX OF RATS WITH PRIMARY AND REPEATED STROKE - Koldunov, V.V.; Bibikova, V.N. (World of Medicine and Biology, 2013)
The dynamics of morphological changes in rat brain in experimental primary and secondary hemorrhagic stroke was establish. Repeated simulated stroke 1 month after the initial stroke. Histological evaluation was performed on the 3th, 21th day, after 3 and 6 months after stroke in a test area the size of 1-2 mm. Degenerative dameged modified neurons with signs of cytolysis, kariolisis with homogeneously colors acidophilic nuclei or with signs piknozis. Are studied structurally-morphological changes at primary and repeated hemorrhagic stroke. The pathogenesis of primary and repeated hemorrhagic stroke is characterized by progressive dynamics of brain tissue edema and degenerative changes. When repeated stroke reliable growth changes in the cerebral cortex exacerbates neurological deficit, is an unfavorable factor recovery period and requires further study of the pathophysiological level.